Variability in salt tolerance in seedlings of panicum coloratum var. makarikariense l. in hydroponics - Cardamone, Luisina (2015)
Fil: Cardamone, Luisina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.